KUASA PEREMPUAN KOREA MODERN DALAM ALBUM TO ANYONE OLEH 2NE1: KRITIK SASTRA FEMINIS KAJIAN - , DESAK MADE ANISA PRATIWI; , Cahyaningrum Dewojati, S.S., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The songs in To Anyone album are the projection of woman's inner strength. The projection of women's inner strength becomes the object of the study. It was seen from how the lyrics reveal the power and the independence of woman. The modern concepts of the songs themselves show up about how woman can live and overcome problems without her boyfriend. This study has two objectives. Firstly, to identify the meaning contained in the lyrics of To Anyone albumâs songs. Secondly, to identify feminist idea on the album. The meaning of four 2NE1 songs conducted with Riffatere Semiotics. Riffatere semiotic reading that be used on this study are heuristic, and hermeneutic. Determination of feminist ideas conducted with the study of feminist literary criticism. Based on the results of Riffatere semiotic, and feminist literary criticism on the four samples, the songs on this research tell about the woman's domination in a romantic relationship. Resistant strength of woman arises from the problems when having a relationship. Feminist ideas of To Anyone album are strong woman, womanâs resistance against the manâs affair, womanâs courage to express her anger, womanâs courage to express her disinterest, womanâs right to make her own decision, and whether woman has her self-esteem, and woman have the right to educated. Conclusion of this research are woman dares to fight against man domination in relationship. Woman also has boldness in expressing their feelings, and their anger. Feminist ideas in the lyrics of To Anyone album are expected to be a guide for woman finding their ways out in dealing with manâs domination in a romantic relationship.